Legal Governance of Islamic Financial Intermediation for Sustainable Agriculture: Regulatory Fragmentation in Indonesia (Contrarius Series: Law & Social Justice, 2026)
This study examines the transformation of Islamic financial intermediation as a legal governance issue, focusing on regulatory coherence between sharia banking law and sustainable agricultural policy in Indonesia. It assesses the implementation of Salam–Istisnāʿ financing under Law Number 21 of 2008 on Sharia Banking and Law Number 41 of 2009 on Sustainable Food Agricultural Land (LP2B). Using a mixed socio-legal approach, the study analyses Financing to Deposit Ratio (FDR) and financial literacy as determinants of community acceptance of Istisnāʿ–Salam financing, based on survey data from farmer groups in West Nusa Tenggara. The findings indicate that both FDR and financial literacy have a positive and significant effect on public acceptance of productive Islamic financing. However, the study also identifies structural regulatory misalignment across Islamic banking regulation, sustainable finance policy, sharia governance, prudential supervision, and agricultural land protection. To capture this condition, the research introduces a Regulatory Fragmentation Index (RFI) as an analytical framework to explain why productive sharia contracts remain underutilised despite formal legal recognition. The study concludes that the effectiveness of Islamic financial intermediation is determined primarily by the coherence of legal governance structures rather than contractual availability or market preference, and argues that regulatory harmonisation is essential to operationalise productive Islamic financing in support of sustainable agricultural development.